2023
DOI: 10.1108/k-08-2022-1172
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing or in-house manufacturing in Hi-tech industry: supply chain process with Delphi-AHP approach

Abstract: PurposeTechnological advancements have benefited businesses all over the world in how they set up production lines, create new products/services and trade goods. Multinational corporations can communicate instantly with their distant operations by utilizing information technology tools and communication networks. Businesses have taken a significant shift and new factors have emerged which affect company's competitiveness. In case of resorting to an outsourcing option, a comprehensive approach for valuing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Article [12] provides key information on this choice in the high-tech industry. According to the study, outsourcing can be more advantageous than inhouse production.…”
Section: Outsourcing In the Production Processmentioning
confidence: 99%
“…Article [12] provides key information on this choice in the high-tech industry. According to the study, outsourcing can be more advantageous than inhouse production.…”
Section: Outsourcing In the Production Processmentioning
confidence: 99%
“…Numerous studies have suggested that good service quality is an important factor during the evaluation and selection of 3 PLs. Cost, quality, and delivery were the attributes looked at by Qureshi et al [ 66 ], which led to the conclusion that it could be helpful to decision-makers in selecting appropriate suppliers based on these attributes. Choosing the supplier who offers the best value for the highest quality product would be best.…”
Section: Introductionmentioning
confidence: 99%